How children's anxiety symptoms impact the functioning of the hypothalamus–pituitary–adrenal axis over time: A cross-lagged panel approach using hierarchical linear modeling. (2nd April 2018) - Ma, Denise; Serbin, Lisa A.; Stack, Dale M.
Abstract: Anxiety symptoms in childhood and adolescence can have a long-term negative impact on mental and physical health. Although studies have shown dysregulation of the hypothalamus–pituitary–adrenal axis is associated with anxiety disorders, it is unclear how and in what direction children's experiences of anxiety symptoms, which include physiological and cognitive–emotional dimensions, impact the functioning of the hypothalamus–pituitary–adrenal axis over time. We hypothesized that higher physiological symptoms would be contemporaneously associated with hypercortisolism, whereas cognitive–emotional symptoms would be more chronic, reflecting traitlike stability, and would predict hypocortisolism over time. One hundred twenty children from the Concordia Longitudinal Risk Research Project were followed in successive data collection waves approximately 3 years apart from childhood through midadolescence. Between ages 10–12 and 13–15, children completed self-report questionnaires of anxiety symptoms and provided salivary cortisol samples at 2-hr intervals over 2 consecutive days. The results from hierarchical linear modeling showed that higher physiological symptoms were concurrently associated with hypercortisolism, involving cortisol levels that remained elevated over the day. In contrast, longitudinal results over the 3 years between data collection waves showed that chronic worry and social concerns predicted hypocortisolism, showing a low and blunted diurnal cortisol profile. These results have implications for broadening our understanding of the links between anxiety, the stress response system, and health across the course of development.